Evaluasi dan Optimalisasi Kinerja Crusher Lsc VI Dalam Upaya Memenuhi Kebutuhan Batu Gamping pada Storage Indarung VI , PT Semen Padang - Agung Wijaya; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2018)
Abstract: PT. Semen Padang has just built a new crusher, productivity of 9475 tons / day to meet the production needs of the Indarung VI plant, but in reality the performance of the LSC VI Crusher is not optimal. For this reason, Crusher LSC VI performance evaluation is needed to determine the factors. In mechanical equipment productivity there are many factors that can influence, among others: work efficiency, operator efficiency, availability of equipment, acceleration of equipment, altitude of sea level, material type, road conditions, cycle time, etc. The actual productivity of the Komatsu HD 785-7 transport equipment for feeding material to the Limestone Crusher VI was 170.47 tons / hours but the loading and hauling ratio currently applied has not been able to meet the feed target for the Limestone Crusher of 1500 tons / hour. The actual productivity of Limestone Crusher VI is 1212.09 tons / hour and its effective production is 7655.98 tons / day. Productivity and actual effective production have not been able to meet the productivity target of 1500 tons / hour and an effective production target of 9475 tons / day. The actual tool availability of the Limestone Crusher VI includes mechanical availability of 79.50%, physical availability of 87.22%, use of available of 56.80%, and effective utility of 49.54%.Keyword : Crusher, Optimalitation, Produktifity, Belt Conveyor, Loading Hauling